Stopping Powers of Alpha Particles in Some Gases At Energies From 1.0 to 6 MeV - Khiem, Le Hong; Trong, Tran Dinh; Nghia, Nguyen The (Communications in Physics, 2016)
Stopping powers of \(α\)-particles emitted by \(^{148}\)Gd, \(^{241}\)Am and \(^{243}\)Cm isotopes in PR10 and isobutane\break (C\(_{4}\)H\(_{10}\)+Ar) gases have been experimentally measured in the energy region from 1.0 to 5.5 MeV. The experimental data were compared with those calculated by SRIM-2013 computer code. It was concluded that the experimental stopping powers in our investigated region are in agreement with the calculated values.